Prevention of weight gain during self-isolation in COVID-19 pandemic era: a narrative review - Harry Freitag Luglio Muhammad (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
COVID-19 is a disease that has affected millions of people worldwide and made a significant impact on health, social life, and economy. One of the strategies to prevent the spread of this virus is through self-isolation. Although this strategy is efficient to prevent a drastic spread of the disease, there are some consequences related to this measure, including social, psychological, and economic impacts. In this review, the author proposes the possibility that this measure could increase the global prevalence of obesity. This might be due to a reduction in total physical activity because of limitations in outdoor activities, increased binge eating because of psychological stress or boredom, and tendency to eat ultra-processed foods and beverages because of limitations in shopping ability. Obesity itself is reported to be one of the risk factors for the severity of COVID-19 infection. Reports from United Kingdom and the United States of America revealed that those with higher body mass index had a higher risk to be treated at an intensive care unit. Therefore, prevention of a significant weight gain might be important to reduce the risk of fatality due to COVID-19. While the global prevalence of obesity is increasing worldwide, it might be important to address this issue at this point in time. Lastly, this review also provides some suggestions to ameliorate the weight gaining effect of self-isolation during the COVID-19 pandemic.